Traditional birth attendants' experiences during the provision of post-natal care in Mopani District, Limpopo province of South Africa - Roinah N. Ngunyulu; Fhumulani M. Mulaudzi; Mmampheko D. Peu (AOSIS, 2020)
Background: South African maternity care guidelines stipulate that post-natal patients can be discharged within 6 h after delivery, provided that the condition of mothers and neonates do not require medical, surgical or obstetric attention. Hence in many instances post-natal care is rendered at home by traditional birth attendants (TBAs). Traditional birth attendants play a crucial role in the care of women during pregnancy, birth and puerperium within communities. Aim: To explore and describe the experiences of TBAs during the provision of post-natal care to mothers and their neonates in order to make recommendations to improve the quality of post-natal care delivered at home. Setting: The community hall of a selected rural traditional community was used as a setting for data collection. Methods: A qualitative, exploratory and descriptive design was used. Three focus groups were held with 26 TBAs whom were purposively selected. Data were analysed using qualitative content analysis. Results: The study confirmed two categories that included: lack of supportive working relationships between TBAs and midwives and lack of respect of TBAs, by post-natal women. Conclusion: It is evident that the TBAs experienced negative experiences. Therefore, initiation of teamwork, empowerment and confidence development are crucial to improve the working experiences of TBAs during the provision of post-natal care. Quality post-natal care might reduce maternal and neonatal morbidity and mortality rates. Teamwork between TBAs and midwives might be initiated. Continuity of care for post-natal women might be improved.